2020
DOI: 10.1111/aphw.12229
|View full text |Cite
|
Sign up to set email alerts
|

Active Today, Replenished Tomorrow? How Daily Physical Activity Diminishes Next‐Morning Depletion

Abstract: Background Physical activity is a salient input to psychological health and well‐being. Recent applied psychology research suggests that physical activity of a greater intensity is particularly important for recovery from work‐related effort expenditure. However, whether and how moderate‐to‐vigorous levels of physical activity influence recovery outside of working populations remains unclear. Further, the process through which this relationship unfolds on a day‐to‐day basis has yet to be mapped. Method We cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Scholars have long recognized that both depletion and voice behavior could be conceptualized as within‐person phenomena that fluctuate daily (Liu et al, 2017). For example, research on depletion has demonstrated that depletion varies between days (Li et al, 2019; Wehrt et al, 2020) as a result of a variety of factors, including sleep (Barnes et al, 2011), late‐night smartphone use (Lanaj et al, 2014), aversive morning commutes (Gerpott et al, 2021), morning routine disruption (McClean et al, 2021), childcare‐related demands (Dettmers et al, 2020), work‐related worry and planning (Casper & Sonnentag, 2020), and physical activity during the previous day (Rost et al, 2021). Likewise, voice research shows that employees may speak up with new ideas or suggestions (i.e., daily promotive voice) and/or express issues, concerns, or problems (i.e., daily prohibitive voice) more on some days than on others (Li et al, 2019; Lin & Johnson, 2015; Liu et al, 2017; Welsh et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have long recognized that both depletion and voice behavior could be conceptualized as within‐person phenomena that fluctuate daily (Liu et al, 2017). For example, research on depletion has demonstrated that depletion varies between days (Li et al, 2019; Wehrt et al, 2020) as a result of a variety of factors, including sleep (Barnes et al, 2011), late‐night smartphone use (Lanaj et al, 2014), aversive morning commutes (Gerpott et al, 2021), morning routine disruption (McClean et al, 2021), childcare‐related demands (Dettmers et al, 2020), work‐related worry and planning (Casper & Sonnentag, 2020), and physical activity during the previous day (Rost et al, 2021). Likewise, voice research shows that employees may speak up with new ideas or suggestions (i.e., daily promotive voice) and/or express issues, concerns, or problems (i.e., daily prohibitive voice) more on some days than on others (Li et al, 2019; Lin & Johnson, 2015; Liu et al, 2017; Welsh et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…In failing to properly stop thinking about their studies, these students often create more work for themselves (Sonnentag & Fritz, 2015), thus increasing their risk of exhaustion and making it harder for them to remain engaged in their studies (Bakker et al, 2014). Supporting these theoretical assertions, research has shown that demands are associated with multiple detrimental outcomes across multiple life areas, including lower levels of engagement in one's education (Rost et al, 2021;Salmela-Aro et al, 2022).…”
Section: Determinants Of Engagement Trajectoriesmentioning
confidence: 99%
“…Employees who plan to engage in WICT may therefore benefit from taking additional measures or apply specific strategies that may limit the negative impact of their WICT. Employees could for instance consciously plan some quality time with the family (Brumley et al, 2021) and/or a physical or social activity (e.g., Rost et al, 2021) in addition to their intended WICT although, of course, more research is needed in this respect. More generally, employees may benefit from limiting their WICT across multiple days since this contributes to higher between-person differences in work-to-home conflict and psychological detachment.…”
Section: Practical Implicationsmentioning
confidence: 99%